Celestial Symbols of the Old Testament in Divine Oikonomia of Salvation - Петровић, Предраг (Sabornost - The Theological Year-book, 2016)
With its visible and invisible dimensions of existence, the heavenly world manifests impalpability, but also the creaturely mode of existence, which opens a perception of multidimensionality of the divine act of creation to a man, different from the superficial, purely sensual perception, which a man prefers to use. Although noticed movements in the heavenly dimensions of the symbolic mode of existence testify about certain habitual movements of the heavenly lights, they also manifest their sense of event. The Old Testament projection of the celestial bodies opens precisely such a sense of event of the heavenly mode of existence which has no fatal, but libertarian features derived from the visible manifestation of the will of God the Creator, Almighty and Savior of the world.